Severe dust storm/thunderstorm activity over Uttar Pradesh on 13th May, 2018 - A case study - GUPTA, J. P.; WARSI, A. H.; SHARMA, PRADEEP (MAUSAM, 2023)
Premonsoon season over Uttar Pradesh is characterized withthunderstorm accompanied with rain, dust storm, gale winds and hail storms etc. These storms generally develop locally in association with convection and moisture convergence and seen as single cells in Doppler Weather Radar, but sometime these thunderstorms are associated with synoptic scale systems viz. Western Disturbance as cyclonic circulation/trough, induced low/ cyclonic circulation or northwest-southeast oriented trough, thereby increasing the spatial extent and severity of these thunderstorms significantly. In the present study, Duststorm/Thunderstorm activity that occurred over the state on large scale on 13th May 2018 and which claimed more than 49 human lives and large number of livestock in Uttar Pradesh has been analyzed. The purpose of this study wasto find out probable dynamic and thermodynamic aspects of this activity. The study indicates that the environment was highly favourable thermodynamically for severe thunderstorm activity with high maximum temperatures (>40C), high CAPE(>1000), high Total Total Index(>50) and high negative Lifted Index values (<-5) over most parts of the northwest Indian plains. The moisture discontinuity line was clearly noticed over south Uttar Pradesh with high moisture contents towards its north. Also 00UTC GFS wind analysis of the day at 925hPa indicated strong southeasterlies of the order of 30-35Kts over Uttar Pradesh resulting high moisture incursion in the lower levels over this region. The Low level wind shear was also high and was about 25-30Kt as evident from Skew-T gram of Lucknow for 12UTC of the day taken from Wyoming site as well as 12UTC wind shear analysis using ERA Interim daily data of ECMWF on 13 May, 2018. These features together with synoptic conditions viz; Western Disturbance (WD) in mid and upper levels and a Cyclonic Circulation (cycir) over south Haryana & neighbourhood as well as an east-west trough extending from this cycir in the lower levels made the environment highly favourable for severe thunderstorm activity over the region.